Analisis Kesalahan Berbahasa Tataran Linguistik pada Cuplikan ada Podcast Arafah Rianti, Halda dan Derbi Romero - Rifky Afriazi; Via Anggita; Adilah Alawiyah; Ai Siti Nurjamilah (Jurnal Pendidikan, Bahasa dan Budaya, 2024)
This study focuses on the analysis of language errors at the linguistic level. It employs a descriptive method to depict an existing and ongoing phenomenon to address the research problem. The process includes a literature review of several journal articles and other sources relevant to the analysis of language errors. Additionally, a video from the TikTok account Pegele, specifically a short video from the ADA Podcast, was used as the analysis material. The video analyzed at the linguistic level was transcribed into written form to facilitate the research process. The short video from the TikTok account Pegele was used as analysis material based on the subtitle textlines included in the video. The study identified several language errors at the linguistic level, including phoneme addition, phoneme reduction, phoneme substitution, affix addition, affix reduction, and affix substitution. These language errors can be attributed to several factors, such as the influence of the mother tongue, limited proficiency in Indonesian, and a lack of formal language instruction. Efforts to reduce linguistic errors in the speech acts performed by Arafah Rianti, Halda, and Derbi Romero in the ADA Podcast program include studying Indonesian sentence structures, expanding vocabulary, and practicing speaking more frequently.